2016
DOI: 10.3390/molecules21091204
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Dietary Constituents in Rosa roxburghii and Rosa sterilis Fruits

Abstract: Both Rosa roxburghii and R. sterilis, belonging to the Rosaceae, are endemic species in Guizhou Province, China. The fruits of these two species are mixed-used as functional food in the region. Aiming to elucidate the phytochemical characteristics of R. roxburghii and R. sterilis fruits, the essential oils and constituents in a methanol extract have been analyzed and compared by GC-MS and UFLC/Q-TOF-MS, respectively. As a result, a total of 135 volatile compounds were identified by GC-MS and 91 components were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 30 publications
(44 reference statements)
1
71
0
Order By: Relevance
“…Therefore, the identification of this kind of compounds will play a pivotal role in elucidating the mechanism of PT. According to the previous research, organic acids showed good MS response in negative ion mode rather than positive ion mode with the characteristic fragment ions such as CO 2 (44 Da), CO (28 Da), and H 2 O (18 Da), which helped rapidly identify compounds (Figure S1B ; Liu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, the identification of this kind of compounds will play a pivotal role in elucidating the mechanism of PT. According to the previous research, organic acids showed good MS response in negative ion mode rather than positive ion mode with the characteristic fragment ions such as CO 2 (44 Da), CO (28 Da), and H 2 O (18 Da), which helped rapidly identify compounds (Figure S1B ; Liu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 86%
“…High-resolution tandem mass spectrometry can provide elemental composition information of both the precursor and product ions, which is very helpful in fragmentation pattern deduction [ 12 , 13 , 14 , 15 , 16 , 17 ] and structural characterization for natural products, such as polyphenols [ 18 , 19 ], flavonoids [ 19 , 20 , 21 ], alkaloids [ 22 ], and terpenes [ 18 , 21 ]. Using this technique, the fragmentation behaviors in the positive ion mode of biflavonoids in the Selaginella genus have been studied [ 23 , 24 ], which will aid in the elucidation of unknown compounds of this kind.…”
Section: Introductionmentioning
confidence: 99%
“…Nature fruits provide the natural nutrients required for neutralizing oxidation attack and attenuating inflammation [21]. R. roxburghii is a native fruit in Southern China and has been used as medicine since 1765 [22]. It is rich in polyphenols, flavonoids, organic acids, triterpenes, amino acids, polysaccharides and essential oils [23,24,25].…”
Section: Introductionmentioning
confidence: 99%